Auditoría de Gestión al Gobierno Autónomo Descentralizado Parroquial de Zambi, Provincia de Loja, periodo 01 de enero al 31 de diciembre de 2022 - Paute Vega, Karla Cecibel (2024)
The present work is entitled Management Audit to the Autonomous Decentralized Parochial Government of Zambi, Loja Province, period January 1 to December 31, 2022. It was framed with the objective of developing the phases of the audit process and preparing the corresponding final report. To carry out the research, a mixed methodology was applied, combining qualitative and quantitative data; in addition, the deductive, inductive, synthetic, and analytical methods for the analysis of the institution and the application of management indicators. The research design was non-experimental, exploratory, and descriptive, with the participation of six members. The results obtained reveal relevant implications in internal control and administrative management, such as the absence of function manuals, monitoring systems, performance evaluation and adequate mechanisms to prevent scams. Based on the above, recommendations arose of including the development of detailed manuals of functions to be fulfilled by the members of the GAD, the realization of periodic internal audits to detect and correct errors, performance to know in which area there is room for improvement, ongoing training of members and the establishment of tools and procedures to improve internal control and transparency of financial operations. These actions seek to improve the efficiency, effectiveness, and transparency of the management of the Zambi Parish GAD, in line with the best practices and regulations established by the Comptroller General State of Ecuador.